2006
DOI: 10.7589/0090-3558-42.3.494
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Low-Level Exposure of the Round Goby (Neogobius Melanostomas) to Clostridium Botulinum Type E Neurotoxin

Abstract: In a 4-mo study (June 2004-September 2004), round gobies (Neogobius melanostomas) were dosed orally every 72 hr for up to 21 days with Clostridium botulinum neurotoxin type E (BoNT/E) at one of four doses: 0, 50, 250, and 500 mouse lethal doses (MLD). Fish were observed for changes in pigmentation and behavior for the duration of the experiment. Mortality was observed with all treatments, with the exception of the 0 MLD control. Clinical signs observed were consistent with prior research and appeared to occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Because many fish in our study were alive, even when harboring free toxin (i.e., in the positive BoNT/E nonfillet samples), our results suggest that similarly affected wild fish could represent a vector for BoNT/E transfer to fish-eating birds in nature. Other work in our lab (14,15) has confirmed that fish can survive for prolonged periods, even after consuming relatively high-and ultimately lethal-doses of toxin. The present study verifies that at least some of this toxin can be present as free toxin in affected fish, either during the living morbidity phase or after death.…”
Section: Public Health Implications the High Proportion Ofmentioning
confidence: 70%
See 1 more Smart Citation
“…Because many fish in our study were alive, even when harboring free toxin (i.e., in the positive BoNT/E nonfillet samples), our results suggest that similarly affected wild fish could represent a vector for BoNT/E transfer to fish-eating birds in nature. Other work in our lab (14,15) has confirmed that fish can survive for prolonged periods, even after consuming relatively high-and ultimately lethal-doses of toxin. The present study verifies that at least some of this toxin can be present as free toxin in affected fish, either during the living morbidity phase or after death.…”
Section: Public Health Implications the High Proportion Ofmentioning
confidence: 70%
“…Since 1999, large-scale type E botulism epizootics have occurred in fish-eating birds on the Great Lakes, primarily Lake Erie. What is unique about these outbreaks is that the avian species mainly involved are known to consume only live fish, and it is hypothesized that the live fish are vectoring the toxin from its point of origin (most likely present as preformed free toxin in the food items eaten by these fish, such as in other smaller fish, invertebrates, sediment, or decaying organic material) to the birds (14,15). To fully understand the potential risk of consuming fish caught during type E botulism epizootics, and if the fish are vectoring toxin to the birds, it is necessary to determine if free BoNT/E is present in fish that have been exposed to BoNT/E.…”
mentioning
confidence: 99%
“…It should be considered that only free BoNT circulating in blood can be detected after injection into bioassay animals. 26 To produce its toxic effect, BoNT must bind to its substrate at the neuromuscular junction, and the bound BoNT is not free to circulate in blood. 13,19,21 Therefore, the quantity of free BoNT in the sera used for the catfish bioassay and Endopep-MS assay was likely less than the original blood concentration that killed the affected catfish.…”
Section: Discussionmentioning
confidence: 99%
“…This method can detect BoNT at levels comparable with or lower than levels detected with mouse bioassays. 1,2,[15][16][17] The use of fish bioassays to establish LD 50 s and sensitivities for botulinum has been described, 6,25,26 but no fish neutralization bioassays have been reported. This manuscript reports a catfish neutralization bioassay confirmed by Endopep-MS to link botulinum in the syndrome of VTC.…”
Section: Discussionmentioning
confidence: 99%
“…Neogobius melanostomus is a probable vector because it spends almost 100% of its time near the lake bottom (Jude et al , 1992; Charlebois et al , 1997) where C. botulinum is more likely to be present (Yule et al , 2006 a ) and are especially abundant in shallow waters where most seabirds feed. Neogobius melanostomus is also sensitive to low levels of chronic exposure to botulism toxin (Yule et al , 2006 b ) and is very abundant in areas where bird mortalities occur, with densities reported to surpass 100 fish m −2 in some areas (Corkum et al , 1998; Steinhart et al , 2004 a ). Fish‐eating birds favour prey whose swimming behaviour makes them easier to capture (Barr, 1973) and infected N. melanostomus exhibit hyperpigmentation and erratic swimming during the last few hours before death, making infected fish stand out as easy prey targets (Yule et al , 2006 a ).…”
Section: Ecological Effectsmentioning
confidence: 99%